2003
DOI: 10.1172/jci17995
|View full text |Cite
|
Sign up to set email alerts
|

Alimentary tract innervation deficits and dysfunction in mice lacking GDNF family receptor α2

Abstract: Subsets of parasympathetic and enteric neurons require neurturin signaling via glial cell line-derived neurotrophic factor family receptor α2 (GFRα2) for development and target innervation. Why GFRα2-deficient (Gfra2 -/-) mice grow poorly has remained unclear. Here, we analyzed several factors that could contribute to the growth retardation. Neurturin mRNA was localized in the gut circular muscle. GFRα2 protein was expressed in most substance P-containing myenteric neurons, in most intrapancreatic neurons, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 42 publications
5
45
0
Order By: Relevance
“…This finding is consistent with previous reports that GFRα2 is present in glial cells located in the mucosal and muscle layers of mouse small intestine (Rossi et al 2003) and in glial cells located in several mouse pelvic organs (Wanigasekara et al 2004). Results from our doublelabeling experiments indicate that GFRα2-positive cardiac Schwann cells are associated with cholinergic and noncholinergic nerve fibers.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding is consistent with previous reports that GFRα2 is present in glial cells located in the mucosal and muscle layers of mouse small intestine (Rossi et al 2003) and in glial cells located in several mouse pelvic organs (Wanigasekara et al 2004). Results from our doublelabeling experiments indicate that GFRα2-positive cardiac Schwann cells are associated with cholinergic and noncholinergic nerve fibers.…”
Section: Discussionsupporting
confidence: 93%
“…5d-f). Because of the identification of GFRα2 in Schwann cells in other tissues (Rossi et al 2003;Wanigasekara et al 2004), additional double-labeling experiments were performed by using antibodies to the Schwann cell marker S100 and to GFRα2. These experiments showed that Schwann cells and their processes were common in the left ventricular wall (Fig.…”
Section: Localization Of Gfrα2 and Ret To Neuronal Cell Bodies In Intmentioning
confidence: 99%
“…A deficiency of NRTN or of its corresponding receptor complex GFRa2 also results in abnormalities of the enteric nervous system (ENS), which are less severe than those obtained by gdnf and its receptor ablation, such as reduced myenteric plexus innervation and abnormal gastrointestinal motility (Heuckeroth et al 1999;Rossi et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Another Ret ligand, neurturin (NTN), has also been implicated in HSCR [121]. The co-receptor for NTN is GFRα2 and, similar to GDNF and GFRα1, mice with mutations in Ntn or GFRα2 exhibit defects in ENS formation [122,123].…”
Section: Hirschsprung Diseasementioning
confidence: 99%